PENGEMBANGAN MODUL BELAJAR SUJUD TILAWAH BERBASIS VIDEO TIKTOK PADA SISWA KELAS VII SMPN 1 PURWOSARI - Pramudita, Ayu Sekarwati; Yusuf, Achmad; Yusuf, Wiwin Fachrudin; Saifulah, Saifulah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Success in the teaching and learning process between teachers and students can be achieved using supporting learning media. To achieve this success, media that follows the objectives and is practical is needed. Increasing student response and interest in learning following student thinking is the purpose of creating learning media. This study aimed to determine the effectiveness of TikTok-based learning modules with grade VII tilawah prostration material. This development resulted in learning media in the form of TikTok video-based modules as a substitute for textbooks to attract student interest and facilitate the learning process for teachers and students. This study is development research with the ADDIE model consisting of five stages: analysis, design, development, implementation, and evaluation. The results of the feasibility test show that the validation test of learning material experts obtained around 85% of its value in the very feasible qualification category. 90% of respondents to validate media teaching materials have a very workable qualification level. Before the media trial on students, the test value for the feasible qualification level was around 61%. After the media trial on students, the qualification level was around 80%. It can be said that the TikTok video-based learning module on the material of tilawah prostration for grade VII junior high school students is worthy of being used as a learning medium.